Health Servive The Language Evaluation On The Effects Of Educational Game For Early Childhood - dony putra dony; Hendro Prasetyo; Widatul Wahidah (Health Media, 2021)
Abstract written in Indonesian and English written explicitly with the background structure, research objectives, research methods, findings and conclusions. Abstract must be written in 150 – 250 words which has no reference. Language skill must be owned by every child. While 2014 in Indonesia, problems language developmental experience 6-19% toddler. As much 32 toddler have problem language development visit everyday in Poli tumbuh kembang anak RSUD dr. Soetomo Surabaya. In Jember, language disorders experienced by 8% of preschool. The children that has slowness experience language has effect experience delays in their cognitive, sensorimotor, psychological, emotional, and child’s environment. The purpose of this research is to know the difference of early childhood language development before and after APE (finger puppet). The design of this research is Quasy experiment with one group pretest posttest. The sampling technique using simple random sampling, samples are taken random by lottery. Total population of 32 children and sample of 30 children. The instrument used is an observation sheet in the form of a checklist of language development assessment. Statistical analysis using wilcoxon signed ranks test. The results showed after given APE (finger puppets) total of children with very good developing category increased from 3.4% to 46.7%. Results wilcoxon signed ranks test program SPSS version 22.0 obtained p value 0.000 of p < 0.05 which means H0 rejected and Ha accepted there is difference of language development of early child after giving APE (finger puppet) in PAUD Alamanda 46 Jember. APE (finger puppet) one of alternative for increase language development. So it is recommended for teachers give story with finger puppets twice a week and parents to start story with finger puppets of two years olds.